Concentrações séricas de 25-hidroxivitamina D e suas associações com intolerância à glicose em uma população indígena, os índios Xavante - Abrahao, Giovanna Campos Paranhos [UNIFESP] (2020)
Background and aims: Type 2 diabetes is a multifactorial disease resulting from diverse genetic and environmental factors as well as the interaction between them. Low levels of 25-hydroxyvitamin D [25(OH)D], an indicator of vitamin D status, have been associated with an increased risk of type 2 diabetes, but not consistently. Also, it remains to be determined if this association differs among ethnic groups. Therefore, we aimed to evaluate vitamin D status and its association with glucose intolerance in a Brazilian indigenous population, the Xavante Indians. Methods: The study population consisted of 819 full Xavante Indians (410 women), aged !18 years and living in two indigenous reserves located in Mato Grosso State, central region of Brazil. Clinical examination and anthropometrical measurements were made, blood samples were obtained for total cholesterol, HDL-cholesterol, triglycerides and 25(OH)D measurement. Fasting and 2-h post 75 g oral glucose load capillary glucose was measured. Vitamin D status was defined by serum 25(OH)D levels: vitamin D sufficiency (25(OH)D: 30e100 ng/mL), vitamin D insufficiency (25(OH)D: 20- <30 ng/mL) and vitamin D deficiency (25(OH)D: < 20 ng/mL). Multiple logistic regression was performed to identify independent associations between 25(OH)D levels and impaired glucose tolerance or diabetes mellitus. Results: Analyses stratified by 25(OH)D levels shows that 65.5% of the population had vitamin D deficiency/insufficiency (25(OH)D < 30 ng/mL). 25(OH)D concentrations were lower in individuals with impaired glucose tolerance or diabetes mellitus than in normal glucose tolerant individuals. Multiple logistic regression analysis showed an inverse association between increments of 25(OH)D and presence of diabetes mellitus (OR per 1 ng/mL increase in 25(OH)D: 0.97; 95% confidence interval: 0.95e0.99), or impaired glucose tolerance (OR per 1 ng/mL increase in 25(OH)D: 0.87; 95% confidence interval: 0.85 e0.89), in an age, sex, BMI and season of sampling-adjusted model. Conclusions: The present population-based study found a high prevalence of hypovitaminosis D among Xavante Indians. In this at-risk population of type 2 diabetes, a significant association of higher serum 25(OH)D with a decreased prevalence of diabetes mellitus and impaired glucose tolerance was observed.